ANALISIS FILSAFATI PENDIDIKAN BERBASIS LIBERAL-PROGRESIVISME - Supriyono Purwosaputro (FPIPSKR Universitas PGRI Semarang, 2023)
The independent campus curriculum and independent learning are currently triggering changes in the education system in Indonesia. The reason is, the competence of students in Indonesia is not all ready to undergo this system change. On the other hand, there is also a dilemma faced by educators who are